Analysis Disclosure of Financial Statements and Factors That Influence: Disclosures in Islamic Firm in Indonesia - Mahsun Mahsun (Universitas Alma Ata, 2020)
Financial Statement Diclausure”is a corporate report disclosure concept. One of the instruments used in company report disclosures involves corporate social environmental responsibility. Then the purpose of this study”is to reveal corporate social responsibility”such as Company Size, Profitability, Leverage, Share Ownership, and Liquidity that can influence the Financial Statement disclosure in sharia companies listed in”the Jakarta Islamic Index (JII) for the 2015-2018 period. This type of research is quantitative”research. Sampling using a proposive sampling method with sampling based on certain criteria, to obtain samples in this study were 10 companies registered in the Jakarta Islamic Index (JII) from 2015-2018. The data used is secondary data from the company's annual financial statement data from 2015-2018.”The data analysis technique uses multiple linear regression. As for the results of the study, it shows that partially”company size, profitability and leverage variables affect the disclosure of Financial Statement on companies listed in JII for the period of 2015-2018. While the share ownership and liquidity variables do not affect the disclosure of Financial Statement for companies listed in JII for the period of 2015-2018. The simultaneous variables of company size, liquidity, leverage, share ownership and liquidity affect the Financial Statement disclosure in companies listed on JII for the period 2015-2018. For the results of the test of the coefficient of determination (R square) variable company size, profitability, leverage, share ownership and liquidity can affect the Pengungkapan Laporan Keuangan disclosure in companies listed on the Jakarta Islamic Index (JII) for the 2015-2018 period of 86.3%.”